A Novel Energy-Driven Architecture for Wireless Sensor Networks - Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Khan Z. A.; Rodrigo; C de Lamare; Thompson J. (2017, 2017)
Title screen